Tri-Layer Composite Nanofiber Wound Dressing Incorporating Glucantime and Silver Nanoparticles for Cutaneous Leishmaniasis Management - Topuz, Hilal; Inal, Murat; Turker, Atiye; Toprak, Zisan; Abamor, Emrah Sefik; Canim Ates, Sezen; Acar, Serap (MDPI, 2026)
Cutaneous leishmaniasis is a zoonotic disease caused by Leishmania parasites and leads to chronic, non-healing skin lesions. Although current drugs can control the disease, their use is limited by systemic side effects, low efficacy, and inadequate lesion penetration. Therefore, innovative local delivery systems are required to enhance drug penetration and reduce systemic toxicity. To address these challenges, silver nanoparticles (AgNPs) were synthesized using propolis extract through a green synthesis approach, and a tri-layer wound dressing composed of polyvinyl alcohol and gelatin containing synthesized AgNPs and Glucantime was fabricated by electrospinning. Characterization (SEM-EDX, FTIR, TGA) confirmed uniform morphology, chemical structure, and thermal stability; the wound dressing exhibited hydrophilicity, antioxidant activity, and biphasic release. Biological evaluations against Leishmania tropica demonstrated significant antiparasitic activity. Promastigote viability decreased from 76.3% in neat fibers to 31.6% in nanofibers containing AgNPs and 7.9% in tri-layer nanofibers containing both AgNPs and Glucantime. Similarly, the amastigote infection index dropped from 410 in controls to 250 in neat nanofibers, 204 in AgNPs-containing nanofibers, and 22 in tri-layer nanofibers containing AgNPs and Glucantime. The tri-layer nanofibers demonstrated enhanced antileishmanial activity over AgNPs-containing fibers, confirming synergistic efficacy. All nanofibers were biocompatible, supporting their use as a safe platform for cutaneous leishmaniasis treatment.
Keywords: cutaneous leishmaniasis; electrospinning; glucantime; nanofiber; silver nanoparticles; wound dressing; ANTIBACTERIAL; PROPOLIS; ANTIOXIDANT; MORPHOLOGY; RELEASE; EXTRACT; TROPICA; SYSTEM; MODEL; DRUG; Engineering; Materials Science